2013
DOI: 10.6061/clinics/2013(08)14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of terlipressin and naloxone compared with epinephrine in a rat model of asphyxia-induced cardiac arrest

Abstract: OBJECTIVE:To evaluate the hemodynamic and metabolic effects of terlipressin and naloxone in cardiac arrest.METHODS:Cardiac arrest in rats was induced by asphyxia and maintained for 3.5 minutes. Animals were then resuscitated and randomized into one of six groups: placebo (n = 7), epinephrine (0.02 mg/kg; n = 7), naloxone (1 mg/kg; n = 7) or terlipressin, of which three different doses were tested: 50 µg/kg (TP50; n = 7), 100 µg/kg (TP100; n = 7) and 150 µg/kg (TP150; n = 7). Hemodynamic variables were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
1
0
2
Order By: Relevance
“…Several animal experiments found that the use of vasopressin resulted in improved survival compared with the use of adrenaline in asphyxial cardiac arrest models. [ 32 33 ] Studies comparing the use of a combination of vasopressin, steroids, adrenaline compared with adrenaline alone,[ 34 ] and of cytidine diphosphate choline compared with adrenaline,[ 35 ] did not find better outcomes in the adrenaline groups. For in-hospital cardiac arrest, the rate of ROSC is significantly higher when vasopressin is used compared with epinephrine.…”
Section: Rugsmentioning
confidence: 99%
“…Several animal experiments found that the use of vasopressin resulted in improved survival compared with the use of adrenaline in asphyxial cardiac arrest models. [ 32 33 ] Studies comparing the use of a combination of vasopressin, steroids, adrenaline compared with adrenaline alone,[ 34 ] and of cytidine diphosphate choline compared with adrenaline,[ 35 ] did not find better outcomes in the adrenaline groups. For in-hospital cardiac arrest, the rate of ROSC is significantly higher when vasopressin is used compared with epinephrine.…”
Section: Rugsmentioning
confidence: 99%
“…Σε μια μελέτη παιδιατρικής ενδονοσοκομειακής ανακοπής, η βασοπρεσσίνη σχετίσθηκε με καθυστερημένη επαναφορά αυτόματης κυκλοφορίας, χωρίς όμως να υπάρχει συσχέτιση με την επιβίωση στις 24 ώρες ή με την έξοδο από το νοσοκομείο 37. H τερλιπρεσσίνη χρησιμοποιήθηκε σε μοντέλο ΑΑΑ ποντικού σε σύγκριση με τη ναλοξόνη, την επινεφρίνη και το placebo: Η μέση τιμή αρτηριακής πίεσης στην ομάδα της τερλιπρεσσίνης ήταν υψηλότερες από αυτές της ομάδας επινεφρίνης σε όλες τις χρονικές περιόδους μετά την ΑΑΑ 38. Τα επίπεδα γαλακτικού οξέος ήταν χαμηλότερα στην ομάδα ναλοξόνης από ό,τι στην ομάδα επινεφρίνης.…”
unclassified
“…Σε αυτό το ζωικό μοντέλο, η τερλιπρεσσίνη και η ναλοξόνη ήταν αποτελεσματικοί αγγειοσυσπαστικοί παράγοντες στην ΚΑΑ και παρουσίασαν ευνοικότερο μεταβολικό προφίλ από την επινεφρίνη. Επίσης, η τερλιπρεσσίνη παρείχε καλύτερη αιμοδυναμική σταθερότητα σε σχέση με την επινεφρίνη 38. H τερλιπρεσσίνη, σε αντίθεση με τη βασοπρεσσίνη, δεν έχει λάβει έγκριση στην αντιμετώπιση της ΚΑΑ με βάση τις οδηγίες του European Resuscitation Council.3.2.2.…”
unclassified